The use of visual schedules and work systems to increase the on-task behaviour of students on the autism spectrum in mainstream classrooms - Macdonald, Libby; Trembath, David; Ashburner, Jill; Costley, Debra; Keen, Deb (Wiley, 2018)
Apparent differences in executive function can lead to challenges for students on the autism spectrum in mainstream settings. Difficulties with staying on-task and transitioning between tasks or task elements can interfere with students’ participation in educational activities and lead to stress and anxiety. While the use of visual supports, such as visual schedules and work systems, has been shown to be effective in supporting students to stay on-task in special education and autism-specific settings, there is little research to support the use of these strategies by teachers in mainstream classrooms. This study evaluated the use of visual schedules and work systems in supporting four students on the autism spectrum to stay on-task and work independently in a mainstream setting. These strategies were implemented by teachers as inclusive practices, and evaluated using observations within the natural classroom environment to examine their feasibility in mainstream settings. All participants demonstrated improvements in on-task behaviours. Results for other, secondary, dependent variables were mixed, with some students showing reduced off-task behaviours and increased productivity. The implications for clinical practice and future research directions are discussed.